Electrospun iron-containing sustainable carbon submicron fibers as Fischer-Tropsch catalyst - Rodríguez-Cano, Miguel Ángel; García-Mateos, Francisco José; Valero-Romero, María José; Ruiz-Rosas, Ramiro Rafael; Rosas-Martínez, Juana María; Rodríguez-Mirasol, José; Cordero-Alcántara, Tomás (My University, 2023)
The problems derived from fossil fuels usage such as climate change and energy crises have led to seek for alternatives. Biomass is a renewable source which can be used to produce fuels and olefins via Fischer-Tropsch from synthesis gas. The fixed bed reactors used in this process usually presents pressure drops and heat transfer limitations. In this sense, the use of structured catalytic bed reactor with fibrillar morphology would allow the reduction of these problems. In this work carbon fibers loaded with iron were prepared in just one step and tested as Fischer-Tropsch catalysts in a fixed bed reactor.
Keywords: Fischer-Tropsch; Lignin; Carbon fibers; Electrospinning; Heterogenous catalysis